PLASMA MINERAL PROFILE AND PREGNANCY STATUS IN BUFFALO SUBJECTED TO DOUBLESYNCH IN SUMMER AND WINTER SEASON - KUMAR, P; PANDEY, A K; KUMAR, S; PHULIA, S K; SHARMA, R K; KUMAR, L (The Indian Journal of Animal Reproduction, 2016)
The buffalo subjected to doublesynch protocol in summer (n=20) and winter (n= 25) season were investigated for plasma Zn, Cu, Ca and P at the start of protocol and at AI. The pregnancy rate following protocol was 40% in summer and 48% in winter. In summer, plasma P was low (p<0.05) in buffaloes, irrespective of pregnancy status, as compared to winter season. However, plasma Zn, Cu and Ca had no variation between seasons (p>0.05). Plasma Zn, Cu and P were invariably high, both in pregnant and non-pregnant buffalo, at time of AI (p<0.05). In brief, plasma mineral profile was not apparently related to pregnancy outcome following doublesynch protocol in summer and winter season.